Sequencing and characterization of miRNAs and mRNAs from the longissimus dorsi of Xinjiang brown cattle and Kazakh cattle - Li, Na; Yu, Qun-Li; Yan, Xiang-Ming; Li, Hong-Bo; Zhang, Yang (Gene, 2020)
•The results showed that 1669 genes were differentially expressed.•Additionally, 346 differentially expressed miRNAs were identified.•The expression levels of 19 genes and miRNAs were verified by qRT-PCR. Breed improvement is an important genetic process affecting meat quality. Compared with Kazakh cattle, Xinjiang brown cattle have significantly improved carcass quality and meat quality. To elucidate the molecular mechanisms underlying the improvements in Xinjiang brown cattle and the differences in beef quality between the two breeds, we used RNA-Seq to study differentially expressed genes and miRNAs and regulatory pathways related to adipogenesis, myogenesis and fibrogenesis in the longissimus dorsi muscles of Xinjiang brown cattle and Kazakh cattle. The results showed that 1669 genes were differentially expressed in the longissimus dorsi muscle tissues of Xinjiang brown cattle and Kazakh cattle; 879 genes were upregulated and 790 genes were downregulated in Xinjiang brown cattle compared to Kazakh cattle. These genes were mainly involved in PPAR signaling, unsaturated fatty acid biosynthesis and vascular smooth muscle contraction. Additionally, 346 differentially expressed miRNAs were identified, of which 265 miRNAs were downregulated and 81 miRNAs were upregulated in Xinjiang brown cattle compared to Kazakh cattle. Association analysis of the differentially expressed genes and miRNAs revealed that 86 differentially expressed miRNAs related to adipogenesis were associated with 31 differentially expressed genes, 76 differentially expressed miRNAs associated with myogenesis were associated with 28 differentially expressed genes, and 54 differentially expressed miRNAs associated with fibrogenesis were associated with 19 differentially expressed genes. miRNA-target gene networks were also constructed. Finally, the expression levels of 19 genes and miRNAs were verified by qRT-PCR. Some differentially expressed genes, including FABP4, ACTA2 and ACTG2, were shown to play an important role in beef meat quality. This is the first study to perform transcriptomic analysis of muscle tissues from Xinjiang brown and Kazakh cattle.